A swiftly tilting planet - L'Engle, Madeleine (New York : Square Fish, 2007)
The youngest of the Murry children must travel through time and space in a battle against an evil dictator who would destroy the entire universe.
"A swiftly tilting planet is the third book in Madeline L'Engle's classic Time quintet."--p. 4 of cover.
Includes Go fish: questions for the author.
Accelerated Reader AR
Keywords: Space and time -- Fiction; Fantasy fiction